Persistence of the Swiss Needle Cast Outbreak in Oregon Coastal Douglas-Fir and New Insights from Research and Monitoring. Issue 4 (25th March 2021) - Shaw, David C; Ritóková, Gabriela; Lan, Yung-Hsiang; Mainwaring, Doug B; Russo, Andrew; Comeleo, Randy; Navarro, Sarah; Norlander, Daniel; Smith, Ben
Abstract: Swiss needle cast (SNC), caused by Nothophaeocryptopus gaeumannii, is a foliage disease of Douglas-fir ( Pseudotsuga menziesii ), that reduces growth in native stands and exotic plantations worldwide. An outbreak of SNC began in coastal Oregon in the mid-1990s and has persisted since that time. Here we review the current state of knowledge after 24 years of research and monitoring, with a focus on Oregon, although the disease is significant in coastal Washington and has recently emerged in southwestern British Columbia. We present new insights into SNC distribution, landscape patterns, disease epidemiology and ecology, host-pathogen interactions, trophic and hydrologic influences, and the challenges of Douglas-fir plantation management in the presence of the disease. In Oregon, the SNC outbreak has remained geographically contained but has intensified. Finally, we consider the implications of climate change and other recently emerged foliage diseases on the future of Douglas-fir plantation management.